2012
DOI: 10.1007/s00402-012-1595-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI results after microfracture of osteochondral lesions of the talus

Abstract: After AM of osteochondral lesions of the talus, 18 of 22 patients had no or mild, occasional pain at 2 years follow-up. On MRI, the lesion volume had been reduced and filling with repair tissue was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Twenty-two studies describing the results of BMS for 747 ankles were identified [8, 11, 24, 27, 31, 33, 45, 55, 61, 65, 77, 78, 93, 96, 100, 104, 105, 108, 114, 115, 123, 133]. There were two RCTs, two prospective cohort studies and one retrospective cohort study, three prospective case series, three retrospective comparative studies and eleven retrospective case series.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies describing the results of BMS for 747 ankles were identified [8, 11, 24, 27, 31, 33, 45, 55, 61, 65, 77, 78, 93, 96, 100, 104, 105, 108, 114, 115, 123, 133]. There were two RCTs, two prospective cohort studies and one retrospective cohort study, three prospective case series, three retrospective comparative studies and eleven retrospective case series.…”
Section: Resultsmentioning
confidence: 99%
“…Microfracturing has been described as a treatment option for chondral defects in various studies. The procedure for microfracture in the knee was first published in 1999 [ 3 , 16 – 18 ], with promising long-term results observed in the knee and talus [ 6 , 10 , 12 ]. However, to the best of our knowledge, only a few studies deal with this procedure in the shoulder, with a notable lack of studies investigating the long-term effects of microfracture in this joint.…”
Section: Discussionmentioning
confidence: 99%
“…The success of treatment of OLT with microfracture techniques has been reported in the literature [ 50 , 61 , 78 , 79 , 82 , 83 ]. Beacher et al studied in 45 patients with arthroscopic debridement and microfracture with improvement of functional outcomes (31 of 39 patients had excellent/good Hannover scoring system) and pain relief (mean pre-operative VAS 6.5/10 improved to 2.4/10 post-operatively) at an average follow-up of 5.8 years [ 78 ].…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…They also reported the improvement of functional outcomes in patients who had failed primary microfracture and underwent repeated microfracture in 17 patients (mean improvement of AOFAS scores was 17.2 points) [ 50 ]. Moreover, MRI was used to evaluate OLT after arthroscopic microfracture in 22 patients by Kuni et al They demonstrated significant reduction of the defect size and significant improvement of the functional outcomes (mean AOFAS score was 87.5 points post-operatively) [ 83 ].…”
Section: Surgical Strategiesmentioning
confidence: 99%